Vera Anatolievna Kolesnichenko - Staff of SI «SISJP NAMS», - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
The article is devoted to the well-known scientist, doctor of medical sciences Kolesnichenko Vira Anatolievna, who turned 60 on November 28, 2017.